TanDEM-X: A Radar Interferometer with Two Formation Flying Satellites - Krieger, Gerhard; Zink, Manfred; Bachmann, Markus; Braeutigam, Benjamin; Schulze, Daniel; Martone, Michele; Rizzoli, Paola; Steinbrecher, Ulrich; Antony, John Walter; De Zan, Francesco; Hajnsek, Irena; Papathanassiou, Kostas; et al. (Acta Astronautica, 2013)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurements) is an innovative formation-flying radar mission that opens a new era in spaceborne radar remote sensing. The primary objective is the acquisition of a global digital elevation model (DEM) with unprecedented accuracy (12 m horizontal resolution and 2 m relative height accuracy). This goal is achieved by extending the TerraSAR-X synthetic aperture radar (SAR) mission by a second, TerraSAR-X like satellite (TDX) flying in close formation with TerraSAR-X (TSX). Both satellites form together a large single-pass SAR interferometer with the opportunity for flexible baseline selection. This enables the acquisition of highly accurate cross-track interferograms without the inherent accuracy limitations imposed by repeat-pass interferometry due to temporal decorrelation and atmospheric disturbances. Besides the primary goal of the mission, several secondary mission objectives based on along-track interferometry as well as new bistatic and multistatic SAR techniques have been defined, representing an important and innovative asset of the TanDEM-X mission. TanDEM-X is implemented in the framework of a public-private partnership between the German Aerospace Center (DLR) and EADS Astrium GmbH. The TanDEM-X satellite was successfully launched in June 2010 and the mission started its operational data acquisition in December 2010. This paper provides an overview of the TanDEM-X mission and summarizes its actual status and performance. Furthermore, results from several scientific radar experiments are presented that show the great potential of future formation-flying interferometric SAR missions to serve novel remote sensing applications. © 2013 IAA Published by Elsevier Ltd. All rights reserved.
DLR Import::2019-04-02
Keywords: Digital elevation model; Earth observation; Formation flying; Interferometry; Remote sensing; Synthetic aperture radar (SAR)